Braincase and Inner Ear Anatomy of the Late Carboniferous Tetrapod Limnoscelis dynatis (Diadectomorpha) Revealed by High-Resolution X-ray Microcomputed Tomography - Klembara, Jozef; Ruta, Marcello; Hain, Miroslav; Berman, David S. (Frontiers in Ecology and Evolution, 2021)
The braincase anatomy of the Pennsylvanian diadectomorph Limnoscelis dynatis is described in detail, based upon high-resolution X-ray microcomputed tomography. Both supraoccipitals and most of the prootics and opisthotics are preserved. The known portions of the left prootic, opisthotic, and supraoccipital enclose complete sections of the endosseous labyrinth, including the anterior, posterior, and lateral semicircular canals, the vestibule, the cochlear recess, and the canal for the endolymphatic duct. The fossa subarcuata is visible anteromedial to the anterior semicircular canal. The presumed endolymphatic fossae occur in the dorsal wall of the posteromedial portion of the supraoccipital. Both the fossa subarcuata and the fossa endolymphatica lie in the cerebellar portion of the cranial cavity. In order to investigate the phylogenetic position of L. dynatis we used a recently published data matrix, including characters of the braincase, and subjected it to maximum parsimony analyses under a variety of character weighting schemes and to a Bayesian analysis. Limnoscelis dynatis emerges as sister taxon to L. paludis, and both species form the sister group to remaining diadectomorphs. Synapsids and diadectomorphs are resolved as sister clades in ~90% of all the most parsimonious trees from the unweighted analysis, in the single trees from both the reweighted and the implied weights analyses, as well in the Bayesian tree.